Transient Interlaminar Thermal Stress Analysis of angle-ply Silicon/Lithium Aluminosilicate Composite plate - Mohammad Hassan, Hammed (Anbar Journal of Engineering Sciences, 2009)
This paper deals with the transient interlaminar thermal stress analysis of angle-ply SIC/LAS composite cantilever plate due to sudden change in the thermal boundary conditions .The transient interlaminar thermal stresses are computed by using the finite element method for different intervals of time. The effects of the fiber volume fraction, fiber orientation angle and stacking sequence are studied. The results are compared with previous studies with a good agreement